Selective, Stable, Bias‐Free, and Efficient Solar Hydrogen Peroxide Production on Inorganic Layered Materials. (19th January 2022) - Song, Jaejung; Yu, Je Min; Ahn, Jang Hyuk; Cho, Hyeonjin; Oh, Jiyeon; Kim, Yoon Seo; Kim, Jieun; Ko, Myohwa; Lee, Seong‐hun; Shin, Tae Joo; Jeong, Hu Young; Yang, Changduk; et al.
Abstract: The importance of hydrogen peroxide (H2 O2 ) continues to grow globally. Deriving the oxygen reduction reaction (ORR) toward the 2e – pathway to form H2 O2 is crucial for high H2 O2 productivity. However, most selective electrocatalysts following the 2e – pathway comprise carbon‐containing organic materials with intrinsically low stability, thereby limiting their commercial applicability. Herein, layered double hydroxides (LDHs) are used as inorganic matrices for the first time. The LDH catalyst developed herein exhibits near‐100% 2e – ORR selectivity and stably produces H2 O2 with a concentration of ≈108.2 mm cm –2 photoanode in 24 h in a two‐compartment system (with a photoanode) with a solar‐to‐chemical conversion efficiency of ≈3.24%, the highest among all reported systems. Density functional theory calculations show that 2e – ORR selectivity is promoted by atomically dispersed cobalt atoms in (012) planes of the LDH catalyst, while a free energy gap between the * O and OOH – states is an important factor. Abstract : A highly 2e – oxygen reduction pathway‐selective layered double hydroxide (LDH) catalyst is proposed to increase the yield of H2 O2 production. A two‐compartment photoelectrochemical system with the catalyst can catalyze H2 O2 generation with concentrations of ≈108.2 mm cm –2 in 24 h without any external bias. A solar‐to‐chemical conversion efficiency of ≈3.24% is recorded, which is the highest efficiency among those of all reported systems.